Construction of a hierarchical micro & nanoporous surface for loading genistein on the composite of polyetheretherketone/tantalum pentoxide possessing antibacterial activity and accelerated osteointegration. (9th November 2020) - Mei, Shiqi; Wang, Fan; Hu, Xinglong; Yang, Kong; Xie, Dong; Yang, Lili; Wu, Zhaoying; Wei, Jie
Abstract : SPNG with a micro & nanoporous surface, SO3 H groups, and sustained release of GT exhibited antibacterial activity, cell responses, and accelerated osteointegration. Abstract : Nanoporous tantalum pentoxide (NTP) particles with a pore size of about 10 nm were synthesized and blended with polyetheretherketone (PEEK) to fabricate a PEEK/NTP composite (PN). Subsequently, PN was treated by concentrated sulfuric acid to create a microporous surface (pore size of around 2 μm) on sulfonated PN (SPN), which formed a hierarchical micro & nanoporous surface. Compared with PN, the porous surface of SPN exhibited higher roughness, hydrophilicity, and surface energy. In addition, genistein (GT) was loaded into the porous surface of SPN (SPNG), which showed high GT loading capacity and sustained release of GT into phosphate buffered saline (PBS). Moreover, SPNG revealed excellent antibacterial activity, which inhibited bacterial ( E. coli and S. aureus ) growth in vitro due to the synergistic effects of both sulfonic acid (SO3 H) groups and the sustained release of GT. Compared with PN, SPN significantly improved the adhesion, proliferation, and osteogenic differentiation of bone mesenchymal stem cells in vitro . Moreover, compared with SPN, SPNG further enhances the cell responses. Compared with PN, SPN remarkably improved bone formation and osteointegration in vivo . Furthermore, compared with SPN, SPNG further enhanced the osteointegration. In short, SPNG with a micro & nanoporous surface, SO3 H groups, and the sustained release of GT exhibited antibacterial activity and accelerated osteointegration, which would have tremendous potential as drug-loaded implants for bone substitute.